2006
DOI: 10.1080/10428190500262144
|View full text |Cite
|
Sign up to set email alerts
|

Amylase: A disease activity index in multiple myeloma?

Abstract: This study reports a case of a patient with lambda-light chain multiple myeloma who developed a high hyperamylasaemia of the salivary type during the disease and soon afterwards died. Ectopic production of amylase by myeloma cells has been described in a few cases and demonstrated by tissue culture and immunohistochemical techniques. The common characteristics of these cases were: salivary amylase isoenzyme increase, high tumor mass, extensive extra-medullary spread, extensive bone destruction and poor prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
2
10
0
2
Order By: Relevance
“…The association between malignancy and hyperamylasaemia was first described in a patient with lung cancer in 1951 [3]. Subsequently, an increased ectopic production of amylase has been reported in both epithelial and non-epithelial tumors [4,5,6]. The present report describes a fatal case of a patient presenting marked hyperamylasaemia which appeared at diagnosis and with the relapse of an underlying multiple myeloma.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The association between malignancy and hyperamylasaemia was first described in a patient with lung cancer in 1951 [3]. Subsequently, an increased ectopic production of amylase has been reported in both epithelial and non-epithelial tumors [4,5,6]. The present report describes a fatal case of a patient presenting marked hyperamylasaemia which appeared at diagnosis and with the relapse of an underlying multiple myeloma.…”
Section: Introductionmentioning
confidence: 87%
“…Occasional reports, mostly from Japan, have documented this rare complication in a few cases of multiple myeloma with extramedullary spread [4,5,6,7,8,9,10,11,12,13,14]. Currently, pathogenesis of the hyperamylasaemia-associated myeloma is not well understood [4, 5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that serum amylase activity may be a prognostic index of multiple myeloma disease progression. 11 Ovarian carcinomas 12,13 are also associated with hyperamylasaemia as are some lung tumours. Amylase-producing tumours of the lung are rare and may comprise in total only 1-3% of all lung carcinomas and, in these cases, the salivary amylase isotype is generally found.…”
mentioning
confidence: 99%